Meta Analisis: Pengaruh Pembelajaran Berbasis Etnomatematika Terhadap Prestasi Belajar Matematika Siswa - Dyah Febriyana; Amrina Rizta (Universitas Swadaya Gunung Djati, 2025)
This research aims to examine how ethnomathematics-based learning impacts students' mathematics learning achievement. Collecting information, sorting, coding, and calculating the Effect Size are the research stages that use this meta-analysis method. From the results of the analysis, it was obtained that the average Size Effect was 0.863 and was included in the high category So it can be concluded that ethnomathematics-based learning applied in mathematics learning has a significant impact. Based on the results of the moderate variable analysis, it is known that ethnomathematics-based learning is best applied at the elementary and secondary school levels and can be used to optimize students' creative thinking abilities, learning outcomes, mathematical communication, mathematical understanding and disposition, as well as problem solving skills.